Playground Facilities, Augmented Reality and K3L Training, As well as Making a Video Profile as an Effort to Develop the Potential of Educational Tourism in Kesiman Village - Rizky Eriandani; Esti Dwi Rinawiyanti; Fidelis Arastyo Andono; Argo Hadi Kusumo (Universitas Lancang Kuning, 2023)
Kesiman Village is located in the Trawas District of the Mojokerto Regency in East Java. Kesiman Village possesses unrealized natural potential and is currently attempting to become a tourist village. Therefore, the Community Empowerment Program Team at the University of Surabaya (Ubaya) facilitated the idea. The service team provided Kesiman Village with children's play facilities, including a playground with quite comprehensive play equipment, including swings, suspension bridges, slurutans, and mini wall climbing. In addition, as a safety measure, the Ubaya Team provided supporting equipment such as information boards (posters) with Augmented Reality for playing equipment and medical equipment (P3K). The abstract contains. The Ubaya Team held Occupational Safety, Health, and Environment (K3L) training for staff and villagers in order to support the provision of safe and comfortable educational tours. The Ubaya Team provided separate bins for organic and non-organic waste as well as plastic bottles in addition to playground equipment. With the conclusion of this program, Kesiman Village is expanding and advancing, thereby increasing the villagers' standard of living.